Mineral content of feeds grown at various Kansas locations - Clary, F.G.; Brent, B.E. (Kansas State University. Agricultural Experiment Station, 2011)
Earlier experiments have shown that cattle may perform differently at different Kansas locations. Feeds from four locations (Manhattan, Mound Valley, Colby, and Garden City) were analyzed for several minerals to see if mineral differences might be responsible. Table 4 shows the results for alfalfa hay. Samples were taken at random and no attempt was made to choose particular varieties. Data for FS 1a sorghum silage is shown in table 5. Table 6 shows mineral analyses for two sorghum grain varieties, and one mixed sample (varieties unknown) taken at each location. The K.S.U. agronomy department carries out annual tests on eleven varieties of forage sorghum at four locations (Garden City, Manhattan, Mound Valley, and Colby). The results are in table 7.
Keywords: Beef; Mineral content; Sorghum grain; Alfalfa